OC-017 Gi side effects of cancer chemotherapy- preliminary results of the foccus study. (17th June 2017) - Caley, L; Pittordou, V; Adams, C; Lalji, A; Mohammed, K; Muls, A; Wedlake, L; Andreyev, HJN
Abstract : Introduction: Treatments for cancer can cause a multitude of debilitating gastrointestinal (GI) side effects. Patients are often told these are untreatable. Systematic investigation and management of GI symptoms improves outcomes after radiotherapy. No studies have investigated symptom management in chemotherapy. This prospective study aimed to identify the frequency and range of troublesome GI symptoms during and after cancer chemotherapy and identify treatable causes. Method: GI oncology patients undergoing chemotherapy were eligible. Participants were assessed before chemotherapy and then monthly during and after treatment for one year using the Gastrointestinal Symptom Rating Scale questionnaire and the Bristol Stool Chart. If new troublesome GI symptoms arose, systematic GI investigations were offered following an algorithm. Results: A total of 241 participants enrolled, 85 subsequently withdrew/died. 58% were men. Median age 63 years (range 30–88). 33% of participants had an oesophageal/gastric tumour, 27% colon, 16% rectal, 10% pancreatic, 6% hepatobiliary and 7% other GI sites. At its peak, approximately 20% of participants had moderate or severe change in taste, reduced appetite, early satiety or rectal flatulence, 8% faecal incontinence and 6% steatorrhoea. Overall, 35% reported type 6/7 stool (diarrhoea) and 9% type 1 stool (constipation). Algorithmic investigations identified one new coeliac, 28% had previously unrecognised abnormal thyroid function, 29% abnormal Vitamin B12 levels and 10% exocrine pancreatic insufficiency. 269 breath tests were offered, 224 (83%) were declined. Of the 45 conducted 36% were positive with 84% suggesting small bowel bacterial overgrowth, 9% lactose intolerance, 5% fructose and 2% sucrose malabsorption. There were 279 recommended endoscopic procedures, 249 (89%) were declined. Of the 30 endoscopies conducted, 60% were abnormal with inflammatory changes most commonly being diagnosed. SeHCAT scans (testing for bile acid malabsorption) were offered 146 times and declined 119 times. Of the 27 conducted, 13 (48%) were abnormal. Conclusion: GI symptoms are common and troublesome during chemotherapy for cancer. Simple questionnaires can identify patients requiring investigations. The assumption that GI chemotherapy-induced symptoms are untreatable is frequently incorrect. Investigational algorithms designed for use by non-gastroenterologists are effective, but patients often refuse tests. Active management of GI symptoms may improve outcomes. Further research is urgently required. This study was funded by The Philip Gould Fund and the Biomedical Research Centre at the Royal Marsden Hospital. Disclosure of Interest: L. Caley: None Declared, V. Pittordou: None Declared, C. Adams: None Declared, A. Lalji: None Declared, K. Mohammed: None Declared, A. Muls: None Declared, L. Wedlake: None Declared, H. J. Andreyev Conflict with: GE, manufacturers of SeHCAT provided free product for this study